Hilbert Transform Reveals Unusual Modulation in Delta Scuti Star KIC 10407873 - Haozhi Wang; Ali Esamdin; Chenglong Lv; Lixian Shen; Rivkat Karimov; Shuhrat A. Ehgamberdiev (The Astrophysical Journal)
We report a δ Scuti star, KIC 10407873, exhibiting significant amplitude modulation. Fourier analysis of Kepler long-cadence data (i.e., Q0-Q17, spanning 1471 days) reveals two distinct features: harmonic series of frequencies in the low-frequency region and the frequencies of the split triplet lines in the high-frequency region. Using the Hilbert transform method, we separated the amplitude modulation signals, obtaining precise parameters for the two modulation frequencies. For the harmonic series of frequencies in the low-frequency region, we isolated them through a prewhitening process. Based on the residual segmented spectrum and the phase-folding diagram, we propose that these harmonic series of frequencies may be caused by temperature inhomogeneity on the stellar surface and stellar rotation. The subsequent phase evolution diagrams we generated, combined with LAMOST’s $v\sin i$ data, further support this hypothesis. Consequently, this suggests that the cause of amplitude modulation in the high-frequency region is unrelated to stellar rotation. Finally, we discussed the information potentially carried by the isolated modulation signals, as well as the similarities between the star’s dual-amplitude modulation and the periodically modulated Tseraskaya–Blazhko effect.